The effect of different exposure parameters on radiation dose in digital mammography and digital breast tomosynthesis: A phantom study. Issue 3 (August 2020) - Asbeutah, A.M.; Brindhaban, A.; AlMajran, A.A.; Asbeutah, S.A.
Abstract: Introduction: There are concerns regarding the increase in radiation dose among women undergoing both digital mammography (DM) and digital breast tomosynthesis (DBT). The aim of this study was to evaluate the effect of different exposure parameters on entrance skin dose (ESD) and average glandular dose (AGD) for DM and DBT using a phantom. Methods: The ESD and AGD of 30 DM and DBT (cranio-caudal projection) examinations using a tissue equivalent phantom where acquired using a GE Senographe Essential DM unit. Commercial phantoms were used to simulate three different breast thicknesses and compositions. Tube potential, tube load, and target/filter combinations were also varied with ESD and AGD recorded directly from the DM unit. Comparisons were made using the non-parametric Kruskal Wallis, Mann–Whitney, and Wilcoxon signed rank tests. Results: The individual ESD values for 4 cm, 5 cm, and 6 cm thick phantoms for DM and DBT at Rh/Rh target/filter combination and 30–32 kV/56 mAs levels were 5.06 and 4.18 mGy; 5.82 and 5.08 mGy; and 7.26 and 11.4 mGy, respectively; while AGDs were 1.57 and 1.30 mGy, 1.33 and 1.39 mGy; and 1.29 and 3.60 mGy, respectively. The Kruskal–Wallis test showed a statistically significant difference in AGD for DM (P = .029) but not for DBT (P = 0.368). The Mann–Whitney and Wilcoxon signed rank tests showed no statistically significant difference for ESD or AGD between both DM and DBT techniques (P = .827 and .513). The percentage differences in ESD for phantom thicknesses of 4 cm, 5 cm, and 6 cm between DBT and DM ranged between −21% and 36%; while for AGD between −21% and 64.2%. Conclusions: The ESD and AGD for single view projection in DM and DBT showed differences at 4 and 6 cm breast thicknesses and compositions but not at 5 cm thickness with 30–32 kV and a Rh/Rh target/filter combination. Implications for practice: A fibro-fatty breast results in less radiation dose variations in terms of ESD and AGD between DM and DBT techniques.